ROMAN TRADE ROUTES IN SOUTH INDIA: GEOGRAPHICAL AND TECHNICAL FACTORS (C. 1ST CENT. BC - 5TH CENT. AD) - JEAN DELOCHE (Indian Journal of History of Science, 2010)
The Setusamudram Ship Canal Project is supposed to clear the passage for ships through Adams’s Bridge, between the Indian peninsula and Sri Lanka. The coral reefs of this isthmus have been a hindrance to navigation. This is the reason why, since the beginning of history, the Palghat Gap in South India channelled traffic from the Arabian sea to the east coast, thus asserting itself as a major communication route, beckoning coastal maritime activities. This natural transpeninsular highway played a particularly important role in commerce during Roman times, from the first to the fourth century AD, because it was considered the best alternative to the long coastal route between the Malabar and Coromandel ports. The maritime route through the Mannar Strait, with its sandbanks and rocky islets, obliging vessels to perform a very tedious transhipment of merchandise, was used for Mediterranean trade from the fourth century onwards only.